Investigation of Academic Procrastination and its Dimensions and its Relationship with Academic Performance among Students of Tabriz University of Medical Sciences Iran - Roghayeh Poursaberi (Kerman University of Medical Sciences, 2017)
Background & Objective: Procrastination is often described as a deliberate and irrational delay It is prevalent among students all over the world The aim of this was study to determine the prevalence of academic procrastination among the students of Tabriz University of Medical Sciences Iran in the academic year 20142015 and its correlation with academic performance Methods: This crosssectional study was carried on 150 medical nursing and midwifery students living in the dormitory of Tabriz University of Medical Sciences The subjects were selected through nonprobability sampling The data collection tool used was the Academic Procrastination Scale (APS) designed by Solomon and Rothblum The total reliability of the PAS and the reliability of its subscales were determined using Cronbachs alpha (range: 041078) The data were analyzed using chisquare test and multiple regression analysis Results: According to the results the prevalence of procrastination and its dimensions were 353% 280% 307% and 313% respectively The chisquare test also showed that procrastination in assignments articles and essays preparation and the total score of procrastination had a meaningful negative correlation with the academic performance of the nursing and obstetric students (P < 001) Furthermore the total score of procrastination and its dimensions had significant negative correlation with the academic performance of the whole sample (P < 001) The stepwise multiple regression reveald analysis that the total score of procrastination was the best factor for predicting academic performance Conclusion: The present study results indicated procrastination as the most common cause of reduction of academic performance among students Therefore complementary studies are needed to investigate the causes of academic procrastination